Intranasal delivery of exosomes from human adipose derived stem cells at forty-eight hours post injury reduces motor and cognitive impairments following traumatic brain injury. (November 2021) - Moss, Lauren D.; Sode, Derek; Patel, Rekha; Lui, Ashley; Hudson, Charles; Patel, Niketa A.; Bickford, Paula C.
Abstract: The neuroprotective role of human adipose-derived stems cells (hASCs) has raised great interest in regenerative medicine due to their ability to modulate their surrounding environment. Our group has demonstrated that exosomes derived from hASC (hASCexo) are a cell-free regenerative approach to long term recovery following traumatic brain injury (TBI). Previously, we demonstrated the efficacy of exosome treatment with intravenous delivery at 3 h post TBI in rats. Here, we show efficacy of exosomes through intranasal delivery at 48 h post TBI in mice lengthening the therapeutic window of treatment and therefore increasing possible translation to clinical studies. Our findings demonstrate significant recovery of motor impairment assessed by an elevated body swing test in mice treated with exosomes containing MALAT1 compared to both TBI mice without exosomes and exosomes depleted of MALAT1. Significant cognitive improvement was seen in the reversal trial of 8 arm radial arm water maze in mice treated with exosomes containing MALAT1. Furthermore, cortical damage was significantly reduced in mice treated with exosomes containing MALAT1 as well as decreased MHCII+ staining of microglial cells. Mice without exosomes or treated with exosomes depleted of MALAT1 did not show similar recovery. Results demonstrate both inflammation related genes and NRTK3 (TrkC) are target genes modulated by hASC exosomes and further that MALAT1 in hASC exosomes regulates expression of full length TrkC thereby activating the MAPK pathway and promoting recovery. Exosomes are a promising therapeutic approach following TBI with a therapeutic window of at least 48 h and contain long noncoding RNA's, specifically MALAT1 that play a vital role in the mechanism of action. Highlights: Intranasal delivery of hASC exosomes rescues TBI induced functional deficits. LncRNA MALAT1 regulates inflammation and microglia activation. LncRNA MALAT1 in hASC exosomes regulates alternative splicing of TrkC. Oxidative stress is alleviated by hASC exosomes in microglia and primary neurons. MALAT1 is a predominant driver of hASC exosomes' repair and regeneration ability.